Antibody profiles to plasmodium merozoite surface protein-1 in Cambodian adults during an active surveillance cohort with nested treatment study. (December 2016) - Spring, Michele; Pichyangkul, Sathit; Lon, Chanthap; Gosi, Panita; Yongvanichit, Kosol; Srichairatanakul, Utaiwan; Limsalakpeth, Amporn; Chaisatit, Chaiyaporn; Chann, Soklyda; Sriwichai, Sabaithip; Auayapon, Montida; Chaorattanakawee, Suwanna; et al.
Abstract Background In addition to evidence for a protective role of antibodies to the malaria blood stage antigen merozoite surface protein 1 (MSP1), MSP1 antibodies are also considered as a marker of past malaria exposure in sero-epidemiological studies. Methods In order to better assess the potential use of MSP1 serology in malaria chemoprophylaxis trials in endemic areas, an analysis for the prevalence of antibodies to bothPlasmodium falciparum andPlasmodium vivax MSP142 in healthy Cambodian adults was conducted at two sites as part of an active, observational cohort evaluating the efficacy of dihydroartemisinin-piperaquine (DP) for uncomplicated malaria (ClinicalTrials.gov identifier NCT01280162). Results Rates of baseline sero-positivity were high (59 and 73 % for PfMSP142 and PvMSP142, respectively), and titers higher in those who lived in a higher transmission area, although there was little correlation in titers between the two species. Those volunteers who subsequently went on to develop malaria had higher baseline MSP142 titers than those who did not for both species. Titers to both antigens remained largely stable over the course of the 4–6 month study, except in those infected withP. falciparum who had multiple recurrences. Conclusion These findings illuminate the difficulties in using MSP142 serology as either a screening criterion and/or biomarker of exposure in chemoprophylaxis studies. Further work remains to identify useful markers of malarial infection and/or immunity.